Pengaruh Lingkungan Tempat Tinggal Dan Karakteristik Rumah Tangga Terhadap Munculnya Pekerja Anak Di NTT (Analisis Data Susenas Dan Potensi Desa 2011) - Ardana, I Made Juli; Arjana, I Gusti Bagus; Ramang, Ruslan (Bumi Lestari; Vol 16 No 2 (2016), 2016)
In Nusa Tenggara Timur the appearance of child labour affected by the living environment and the household characteristic. The descriptive analysis showed that in 2011 there were 4,37 % child labour in NTT. The inference analysis showed the probability of children who live in urban area become a child labour was 0,56 times than who live in rural area, the probability of children who live in a region that there was school available become a child labour is 0,43 times than children who live in a region without school. Children with head of household work in formal sector had less probability become a child labour than children with head of household not working/work in informal sector, the probability was 0,47 times. Probability of children with head of household education highschool or above become a child labour 0,58 times than children with head of household education secondary school or less. Probability of children with head of household sex was male become a child labour 0,70 times then whose head of household sex was female. A boy have probability become a child labour 1,36 times than a girl. This result showed that living environment and household characteristics influence the appearance of child labour in NTT.
Keywords: environment; child labour; household characteristics; logistic regression